Structure of the fada-gourma shear zone Eastern Burkina Faso - Sehloho, Pulane Relebohile (My University, 2018)
The Baoulé-Mossi Domain in eastern Burkina Faso is a greenstone belt-granitoid terrane, formed in a volcanic arc tectonic environment. Volcanism and magmatism were coeval at around 2239 Ma, and this formed the basement rocks of the Fada-Gourma Shear Zone (FGSZ) region. Crosscutting relations observed in the field, aided by zircon U-Pb age data reveal that pluton emplacement continued to post-2167±12 Ma. The youngest units are NW-trending dolerite dykes, dated at 1814±26 Ma in eastern Burkina Faso. The study area has five defined deformation events. D1 is responsible for the remnant NW-trending S1 foliation in some of the granite gneisses and the foliated and gneissic granodiorites outside of the shear zones. The σ1 principal compressive stress orientation was NE-SW. The metamorphic grade associated with D1 is amphibolite facies. D2 had a NW-SE oriented compressive stress direction, and this resulted in thrust faulting and the NE-trending dominant structural grain in the study area. The associated metamorphic grade for D2 is lower amphibolite facies. D3 involved a dextral-reverse slip along faults with a NE trend, with southeast-block-up displacement. The principal compressive stress axis was ENE-WSW to ESE-WNW directed. Metamorphic grade associated with D3 is greenschist facies to lower amphibolite facies. D4 caused the sinistral reactivation of the NE-trending D3 structures. The sinistral shear overprint the dextral displacement and a sigmoidal foliation related to D4 is discernible on the aeromagnetic imagery data. The principal compressive stress axis during D4 was NNE-SSW to N-S oriented. The metamorphic grade during D4 was greenschist facies. D5 is a late-stage brittle deformation that led the formation of NW-trending extensional fracture cleavage planes. The imagery data was integrated with field data to aid in establishing the orientation of foliations, and the kinematic and geometric information at map scale and at outcrop scale. Petrographic descriptions provided information at a micro-scale where available. The study area is host to gold mineralization, and there is a network of active artisanal mines in the northern domains of the study area. Tambiga Hill is one of the larger actively mined quartz stockwork vein deposits in the Gourma region. Gold mineralization is concomitant with quartz veins, and is hosted either adjacent to the quartz veins, or within the veins. Gold is either invisible, or occurs as nuggets. Pyrite, tourmaline, ankerite and minor malachite are also present as accessory minerals within the quartz veins. Gold mineralization is associated with the late stages of D2, and D3.
A Dissertation submitted to the Faculty of Science, University of Witwatersrand in the fulfillment of the requirements for the degree of Master of Science 2018
Keywords: Metallogeny; Sedimentation and deposition; Geological time